PP2A inhibition overcomes acquired resistance to HER2 targeted therapy - McDermott, Martina SJ (Mol Cancer, 2014)
BACKGROUND: HER2 targeted therapies including trastuzumab and more recently lapatinib have significantly improved the prognosis for HER2 positive breast cancer patients. However, resistance to these agents is a significant clinical problem. Although several mechanisms have been proposed for resistance to trastuzumab, the mechanisms of lapatinib resistance remain largely unknown. In this study we generated new models of acquired resistance to HER2 targeted therapy and investigated mechanisms of resistance using phospho-proteomic profiling. RESULTS: Long-term continuous exposure of SKBR3 cells to low dose lapatinib established a cell line, SKBR3-L, which is resistant to both lapatinib and trastuzumab. Phospho-proteomic profiling and immunoblotting revealed significant alterations in phospho-proteins involved in key signaling pathways and molecular events. In particular, phosphorylation of eukaryotic elongation factor 2 (eEF2), which inactivates eEF2, was significantly decreased in SKBR3-L cells compared to the parental SKBR3 cells. SKBR3-L cells exhibited significantly increased activity of protein phosphatase 2A (PP2A), a phosphatase that dephosphorylates eEF2. SKBR3-L cells showed increased sensitivity to PP2A inhibition, with okadaic acid, compared to SKBR3 cells. PP2A inhibition significantly enhanced response to lapatinib in both the SKBR3 and SKBR3-L cells. Furthermore, treatment of SKBR3 parental cells with the PP2A activator, FTY720, decreased sensitivity to lapatinib. The alteration in eEF2 phosphorylation, PP2A activity and sensitivity to okadaic acid were also observed in a second HER2 positive cell line model of acquired lapatinib resistance, HCC1954-L. CONCLUSIONS: Our data suggests that decreased eEF2 phosphorylation, mediated by increased PP2A activity, contributes to resistance to HER2 inhibition and may provide novel targets for therapeutic intervention in HER2 positive breast cancer which is resistant to HER2 targeted therapies.